Strategi Peningkatan Produksi Dengan Balanced Scorecard dan ANP - Al Fisimar, Farhan; Aulawi, Hilmi; Aisyah, Risa (Institut Teknologi Garut, 2025)
PT. Antaboga Pangan Nusantara faces a strategic challenge to increase its production capacity from 1,200 pieces per day to 2,500 pieces per day in order to meet its market expansion targets. This study aims to design a comprehensive production capacity improvement strategy by integrating the Balanced Scorecard (BSC) and Analytical Network Process (ANP) methods. The BSC method is used to translate the company's vision into a series of measurable strategic objectives in four perspectives: finance, customers, internal business processes, and learning and growth. Furthermore, the ANP method is used to prioritize these strategic objectives by modeling complex dependencies and feedback relationships between elements. Data was collected through documentation studies, interviews, and paired comparison questionnaires completed by internal company experts. The results of the study showed that strategic objectives in the Internal Business Process perspective, such as Production Flow Optimization and Bottleneck Elimination, had the highest priority at 17%. This is followed by objectives in the Learning and Growth perspective, such as Improving Technical Competence and Workforce Problem-Solving Skills. This integrated framework successfully provides a measurable and implementable strategic roadmap for the company to allocate resources effectively in achieving production capacity targets.